Laparoscopic cholecystectomy in acute cholecystitis: A feasible option regardless of timing - Ramya M Vishweshwara; Mallikarjuna Manangi; Dharini Dharini; C S Santhosh; Sunil V Kumar; M K Ramesh; K Seshagiri Rao (Formosan Journal of Surgery, 2020)
Background: The optimal timing of laparoscopic cholecystectomy (LC) in acute cholecystitis still remains a debate. Recent studies emphasize that LC can be done safely within the 1st week of onset of the disease process. However, not much data are available that defines the “early” period. We observed, in our institute that, patients presenting beyond 1st week with complications or unresolving symptoms. We aim to compare the outcomes of LC performed after 1st week versus interval LC. Materials and Methods: A retrospective study of 64 patients who underwent LC from November 2017 to May 2018 was carried out. The study included one group of 32 patients who underwent LC after the 1st week (Group A) and another group of 32 patients who were operated after an interval of 6 weeks (Group B). Data were collected and compared. Results: The mean duration of surgery (71.09 vs. 84.82 min, P < 0.05), total hospital stay (7.34 vs. 13.40 days, P < 0.05), and overall cost (USD 79.40 vs. 102.34 USD, P < 0.05) was significantly lesser in Group A. Intraoperative difficulty score (5.41 vs. 4.25, P < 0.05) was more in Group A. No complications, mortality, or conversion to open surgery occurred in both groups. A case of gall bladder perforation (at 3 weeks) and Mirizzi syndrome (at 4 weeks) were observed in patients who were in interval period. Four patients in Group B had readmission during the interval period due to biliary colic and were managed conservatively and operated at 6 weeks as planned. Conclusion: LC performed even after 7 days of initial episode scores over interval LC in terms of total hospital stay, cost, morbidity and has the advantage of treating patients who would be lost to follow-up due to neglect, occupational, and financial concerns. Further studies are needed to validate our results.